GEODYNAMIC ANALYSIS OF TOMOGRAPHIC DIAGRAMS - Khain V.Ye.; Zverev A.T. (My University, 1990)
Seismic tomography suggests the existence of broad variations of seismic velocity in the mantle. Regions with moderate velocities occupy a much smaller area than regions with anomalously low or high values. It follows that the dynamics of the mantle are driven by two concurrent global geodynamic processes or systems, namely, heating and cooling (with contraction). Statistical analysis of the tomographic diagrams indicates that zones where heating takes place are located chiefly beneath the oceans. They often cover large areas that encompass volcanic arcs, rift zones and ocean blocks, as well as parts of the continents. At depths of 1300 km or more, the correlation between variations in the seismic wave velocity and the tectonic structures of the lithosphere disappears completely. These facts indicate that the large regions of heat generation in the mantle support the overall functioning of the global geodynamic system, which acquires a specific tectonic expression only in the upper intervals of the mantle.